Darkness falls on the land of light : experiencing religious awakenings in eighteenth-century New England - Winiarski, Douglas Leo (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2017)
"This ... history of popular religion in eighteenth-century New England examines the experiences of ordinary people living through extraordinary times. Drawing on an unprecedented quantity of letters, diaries, and testimonies, Douglas Winiarski recovers the pervasive and vigorous lay piety of the early eighteenth century"--